How to dissociate porcine ovaries: towards efficient retrieval of putative female germline stem cells - Rita L. Sousa; Sandra Farré; Martin Waterfall; Yvonne L. Odey; Kay Samuel; Evelyn E. Telfer; Peter E.J. Bols; Ruth Appeltant (Theriogenology, 2026)

Functional bitter taste signaling and stimulus intensity influence diet-induced salivary protein upregulation - Verenice Ascencio Gutierrez; Kimberly F. Beede-James; Laura E. Martin; Kyle T. Zumpano; Kristen E. Kay; Kathryn F. Medler; Ann-Marie Torregrossa (Appetite, 2026)

Participatory Scenario Design to Support Ex-ante Biodiversity and Ecosystem Services Assessments in Four European Agricultural Case Studies - Katrin Karner; Monika Suškevičs; Florian Danzinger; Sonja Kay; Claudia Bethwell; Noëlle Klein; Takamasa Nishizawa; Johannes Schuler; Michael Glemnitz; Peter Zander; Tobias Conradt; Kalev Sepp; et al. (Environmental Management, 2026)
Anticipating future socioeconomic conditions through scenarios supports effective land-use planning and management that safeguards biodiversity and ecosystem services (BES). This study introduces a novel participatory scenario development protocol to design consistent, nested regional scenarios tailored for BES assessments of agricultural land-use. The protocol is applied in four European case studies (subnational regions in Austria, Estonia, Germany, and Switzerland), combining regional narratives with quantitative developments aligned with the Shared Socioeconomic Pathways for European agri-food systems for 2050 (Eur-Agri-SSPs). Two innovative scenario components are introduced: (i) land-use and management practices and (ii) land-use-biodiversity actions, including private and public instruments. These components are typically neglected in larger-scale scenario applications. Despite shared European boundary conditions from the Eur-Agri-SSPs, the regional scenarios exhibit substantial variation, driven by current land-use structures and stakeholder input. Scenario elements, shaped by existing funding schemes and socioeconomic contexts, vary substantially across scenarios and regions. Examples include the share of organic farms and the level of payments for agri-environment-climate measures. In Münsterland (Germany) and Lääne County (Estonia), current agri-environment payments are significantly lower than in Schwarzbubenland (Switzerland) or the Wienerwald (Austria), and this is reflected in the SSP1 (“..sustainable paths”) and SSP2 (“..established paths”) scenarios. This study demonstrates the value of regional extensions of the SSP framework, grounded in participatory processes, to support context-specific BES assessments. It contributes to scenario research by presenting key challenges and recommendations for nested participatory scenario design and by bridging the gap between global and continental frameworks and subnational implementation needs.

The COSPAR international space weather action teams (ISWAT) initiative: a driving force for the COSPAR space weather roadmap - Maria M. Kuznetsova; Mario M. Bisi; Hermann J. Opgenoorth; Martin A. Reiss; M. Leila Mays; Lucilla Alfonsi; C. Nick Arge; David Barnes; Anna Belehaki; Thomas E. Berger; Amanda Brecht; Sean Bruinsma; et al. (Advances in Space Research, 2026)

Assembly of Medium Progenitor Toxin Complexes and HA Complexes Into a Large Botulinum Neurotoxin Complex - Andreas Rummel; Kwok-ho Lam; Linfeng Gao; Adina Przykopanski; Baohua Chen; Ting Huang; Maren Krüger; Anna-Magdalena Bartels; Martin Bernhard Dorner; Kay Perry; Brigitte Gertrud Dorner; Rongsheng Jin (Toxicon, 2026)

Project Psyche: reference genomes for all Lepidoptera in Europe - Charlotte J. Wright; Niklas Wahlberg; Roger Vila; Marko Mutanen; Pável Matos-Maraví; Kay Lucek; Irena Kleckova; Leonardo Dapporto; Vlad Dincă; Claudia Bruschini; Christopher W. Wheat; Marta Vila; et al. (Trends in Ecology & Evolution, 2025)

Workflow for the Creation of 3D Stereoscopic Models of Supra- and Infratentorial Brain Venous Anatomy and their Integration in a Virtual Reality Environment - Francesco Carbone; Toma Spiriev; Martin Trandzhiev; Michael Wolf-Vollenbröker; Kay M. Körner; Andrea Steuwe; Matteo de Notaris; Vladimir Nakov; Jan F. Cornelius (Neuroinformatics, 2025)

Retrofitted watershed scale green infrastructure reduces heavy metals in urban stormwater from residential land use - Joseph S. Smith; Kay Bernard; Kathryn M. Boening-Ulman; Jay F. Martin; R. Andrew Tirpak; David M. Wituszynski; Ryan J. Winston (Journal of Hazardous Materials, 2025)

Large cobblestone dams for natural flood management in wide peatland gullies - Adam Ryan Johnston; David Brown; Tim Allott; Salim Goudarzi; Martin Kay; David Milledge; Emma Shuttleworth; Tom Spencer; Martin Evans (Ecological Engineering, 2025)

Marine data assimilation in the UK: the past, the present, and the vision for the future - Jozef Skákala; David Ford; Keith Haines; Amos Lawless; Matthew J. Martin; Philip Browne; Marcin Chrust; Stefano Ciavatta; Alison Fowler; Daniel Lea; Matthew Palmer; Andrea Rochner; et al. (Ocean Science, 2025)
In the last 2 decades, UK research institutes have led a wide range of developments in marine data assimilation (MDA), covering areas from operational applications in physics and biogeochemistry to fundamental theory. We highlight the emergence of strong collaboration in the UK MDA community over this period and the increasing unification of its tools. We focus on identifying the MDA stakeholder community and current/future areas of impact, as well as current trends and future opportunities. This includes the rapid growth of machine learning (ML)/artificial intelligence (AI) and digital-twin applications. We articulate a vision for the future, including the need for future types of observational data (whether planned missions or hypothetical) and how the community should respond to increases in computational power and new computer architectures (e.g. exascale computing). We contrast the requirements of different MDA areas, including physics, biogeochemistry, and coupled data assimilation (DA). Although the specifics of the vision depend on each area, common themes emerge. We advocate for balanced redistribution of new computational capability among increased model resolution, model complexity, more sophisticated DA algorithms, and uncertainty representation (e.g. ensembles). We also advocate for integrated approaches, such as strongly coupled DA (ocean–atmosphere, physics–biogeochemistry, and ocean–sea ice) and the use of ML/AI components (e.g. for multivariate increment balancing, bias correction, model emulation, observation re-gridding, or fusion).

Multiple Models of European Marine Fish Stocks: Regional Winners and Losers in a Future Climate - Sévrine F. Sailley; Ignacio A. Catalan; Jurgen Batsleer; Sieme Bossier; Dimitrios Damalas; Cecilie Hansen; Martin Huret; Georg Engelhard; Katell Hamon; Susan Kay; Francesc Maynou; J. Rasmus Nielsen; et al. (Global Change Biology, 2025)
Climate change continues to alter the productivity of commercially and culturally important fisheries with major consequences for food security and coastal economies. We provide the first, multi‐model projections of changes in the distribution and productivity of 18 key fish stocks across seven European regional seas spanning the Mediterranean to the Arctic, using 11 state‐of‐the‐art bio‐ecological models. Our projections indicate species‐ and region‐specific changes in abundance and distributions of these stocks by the mid‐ to late 21st century. The varied responses are caused by differences in species' physiology, regional food web dynamics, and physical habitat characteristics. Important drivers include not only warming of Europe's seas (from 1°C to 3°C in RCP 4.5, and 2°C to 4°C in RCP 8.5 by 2100) and changes in primary productivity but also oxygen‐limited fish growth, changes in pH, and benthic dissolved organic carbon. Warming and altered levels of secondary production are projected to lead to declines in some stocks (Norwegian and Barents Sea herring) and increases in others (Bay of Biscay anchovy). While some temperate and cold‐water stocks are projected to decline markedly in some regions (e.g., North Sea, Western Mediterranean), the immigration of species from the south and/or increase in productivity of warm‐water species may offer new opportunities for fisheries. Species‐level changes will likely have ecosystem‐level consequences that have yet to be fully assessed, and responses in some sub‐areas may be more pronounced due to local processes not captured in projections. Projections are consistent despite differences in model structures, and the results of our multi‐model analysis align with other modelling exercises while delving into details often overlooked at the species or spatial level. This represents a novel approach to projecting the impacts of climate change on fisheries, which should be considered in future efforts to support climate‐ready management strategies for marine fish stocks.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

New particle formation event detection with convolutional neural networks - Xun Zhang; Lijie Wu; Xiansheng Liu; Tao Wang; Marta Monge; Meritxell Garcia-Marlès; Marjan Savadkoohi; Imre Salma; Susanne Bastian; Maik Merkel; Kay Weinhold; Alfred Wiedensohler; et al. (Atmospheric Environment, 2024)

Concordance in dietary intake among caregivers and infants during the period of complementary feeding: A scoping review - Sara V. Bernate Angulo; Brooke T. Nezami; Stephanie L. Martin; Melissa C. Kay; Taylor N. Richardson; Heather M. Wasser (Appetite, 2024)

Results of a Collaborative Study for In Vitro BoNT Activity Determination Using the BINACLE (binding and cleavage) Assay - Heike A. Behrensdorf-Nicol; Ursula Bonifas; Jolanta Klimek; Kay-Martin Hanschmann; Birgit Kegel (Toxicon, 2024)

Stakeholder perceptions of agricultural landscape services, biodiversity, and drivers of change in four European case studies - Monika Suškevičs; Katrin Karner; Claudia Bethwell; Florian Danzinger; Sonja Kay; Takamasa Nishizawa; Johannes Schuler; Kalev Sepp; Rando Värnik; Michael Glemnitz; Maaria Semm; Christina Umstätter; et al. (Ecosystem Services, 2023)

Ambient air particulate total lung deposited surface area (LDSA) levels in urban Europe - Xiansheng Liu; Hadiatullah Hadiatullah; Xun Zhang; Pedro Trechera; Marjan Savadkoohi; Meritxell Garcia-Marlès; Cristina Reche; Noemí Pérez; David C.S. Beddows; Imre Salma; Wanda Thén; Panayiotis Kalkavouras; et al. (Science of The Total Environment, 2023)

Peatland gully restoration with stone and timber dams (Kinder Plateau, UK) - Tim Howson; Martin Evans; Tim Allott; Emma Shuttleworth; Adam Johnston; Joe Rees; David Milledge; Donald Edokpa; Chris Lockyer; Martin Kay; Tom Spencer; David Brown; et al. (Ecological Engineering, 2023)

Active debris removal: A review and case study on LEOPARD Phase 0-A mission - Mithun Poozhiyil; Manu H. Nair; Mini C. Rai; Alexander Hall; Connor Meringolo; Mark Shilton; Steven Kay; Danilo Forte; Martin Sweeting; Nikki Antoniou; Victoria Irwin (Advances in Space Research, 2023)

Anti-apoptotic genes and non-coding RNAs are potential outcome predictors for ulcerative colitis - Wei Meng; Kay-Martin Johnsen; Christopher G. Fenton; Jon Florholmen; Ruth H. Paulssen (Functional & Integrative Genomics, 2023)
Due to the lack of clinical, immunologic, genetic, and laboratory markers to predict remission in ulcerative colitis (UC) without relapse, there is no clear recommendation regarding withdrawal of therapy. Therefore, this study was to investigate if transcriptional analysis together with Cox survival analysis might be able to reveal molecular markers that are specific for remission duration and outcome. Mucosal biopsies from patients in remission with active treatment-naïve UC and healthy control subjects underwent whole-transcriptome RNA-seq. Principal component analysis (PCA) and Cox proportional hazards regression analysis were applied to the remission data concerning duration and status of patients. A randomly chosen remission sample set was used for validation of the applied methods and results. The analyses distinguished two different UC remission patient groups with respect to remission duration and outcome (relapse). Both groups showed that altered states of UC with quiescent microscopic disease activity are still present. The patient group with the longest remission duration and no relapse revealed specific and increased expression of antiapoptotic factors belonging to the MTRNR2-like gene family and non-coding RNAs. In summary, the expression of anti-apoptotic factors and non-coding RNAs may contribute to personalized medicine approaches in UC by improving patient stratification for different treatment regimens.

Impact of Access and Benefit Sharing implementation on biological control genetic resources - Peter G. Mason; Barbara I. P. Barratt; Fernando Mc Kay; Johannette N. Klapwijk; Luciana C. Silvestri; Martin Hill; Hariet L. Hinz; Andy Sheppard; Jacques Brodeur; Marcello Diniz Vitorino; Philip Weyl; Kim A. Hoelmer (BioControl, 2023)
The third objective of the Convention on Biological Diversity, the fair and equitable sharing of benefits arising out of the use of genetic resources was further developed when the Nagoya Protocol on Access and Benefit Sharing came into effect in 2014. Interpretation of how this agreement is being implemented is wide-ranging and there are implications for biological control. A survey of biological control workers indicated that while some countries have facilitated access to biological control genetic resources, requirements in other countries have impeded biological control implementation. There was consensus that benefits to provider countries should be in the form of supporting local research communities. There was also agreement that the free use and exchange of biological control genetic resources has provided benefits to the global community, including to both providers and recipients of the agents. It is recommended that consideration of the free use and exchange principal should be a key element of Access and Benefit Sharing measures for the future.

International agreement for the use and exchange of classical biological control genetic resources: a practical proposal - Peter G. Mason; Fernando Mc Kay; Luciana C. Silvestri; Martin Hill; Philip Weyl; Hariet L. Hinz; Jacques Brodeur; Marcelo Diniz Vitorino; Barbara I. P. Barratt (BioControl, 2023)
The Nagoya Protocol on Access and Benefit Sharing (ABS) was implemented to further develop the third objective of the Convention on Biological Diversity, the fair and equitable sharing of benefits arising out of the utilization of genetic resources. Interpretation of this agreement is wide-ranging and there is concern that if ABS measures are poorly implemented biological control and the resultant public good will be greatly impeded. The ethos of multilateral use and exchange of genetic resources used in classical biological control will be particularly affected. In the spirit of the fair and equitable sharing of benefits arising out of the utilization of genetic resources, we propose a simple practical solution in the form of an international agreement on the use and exchange of classical biological control genetic resources.

EGR3 regulates opioid-related nociception and motivation in male rats - Swarup Mitra; Shruthi A. Thomas; Jennifer A. Martin; Jamal Williams; Kristen Woodhouse; Ramesh Chandra; Jun Xu Li; Mary Kay Lobo; Fraser J. Sim; David M. Dietz (Psychopharmacology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Plant community responses to experimental climate manipulation in a Welsh ombrotrophic peatland and their palaeoenvironmental context - Luke O. Andrews; James G. Rowson; Simon J. M. Caporn; Nancy B. Dise; Eleanor Barton; Ed Garrett; W. Roland Gehrels; Maria Gehrels; Martin Kay; Richard J. Payne (Global Change Biology, 2022)
We test whether vegetation community composition from a 10‐year climate manipulation experiment on a Welsh peat bog resembles vegetation communities during periods of climate change inferred from a peat core. Experimentally warmed and combined warmed and droughted treatments drove significant increases in ericaceous shrubs but Sphagnum was unaffected. Similarly, Calluna vulgaris seeds increase during inferred warmer periods in the palaeoecological record. Experimental short‐term episodic drought (four 4‐week drought treatments) did not affect vegetation. Plant community composition has undergone several abrupt changes throughout the past c. 1500 years, often in response to human disturbance. Only slight changes occurred during the Medieval Climate Anomaly (c. 950–1250 Common Era [CE]) in vegetation and hydrology, while abrupt changes occurred during the Little Ice Age (c. 1300–1850 CE) when water tables were highest, suggesting that these shifts were driven by changes in water table, modulated by climate. A period of water table drawdown c. 1800, synchronous with historical records of increased drainage, corresponds with the development of the present‐day vegetation community. Modern analogues for fossil material, characterized by abundant Rhynchospora alba and Sphagnum pulchrum , are more common after this event. Vegetation changes due to climate inferred from the palaeo record differ from those observed in the experiments, possibly relating to differences in the importance of drivers of vegetation change over varying timescales. Whereas temperature is frequently identified as the dominant driver of plant community change in experiments, sustained changes in water table appear to be more important in the long‐term record. We find evidence that recent climate change and other anthropogenic stressors (e.g. drainage, heavy metal and nitrogen pollution) may promote the development of novel plant communities without analogues in the fossil record. These communities may be poorer at sequestering carbon and may respond differently to future climate change.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Assigning occurrence data to cryptic taxa improves climatic niche assessments: Biodecrypt, a new tool tested on European butterflies - Leonardo Platania; Mattia Menchetti; Vlad Dincă; Cecília Corbella; Isaac Kay‐Lavelle; Roger Vila; Martin Wiemers; Oliver Schweiger; Leonardo Dapporto (Global Ecology and Biogeography, 2020)
Aim Occurrence data are fundamental to macroecology, but accuracy is often compromised when multiple units are lumped together (e.g., in recently separated cryptic species or in citizen science records). Using amalgamated data leads to inaccuracy in species mapping, to biased beta‐diversity assessments and to potentially erroneously predicted responses to climate change. We provide a set of R functions (biodecrypt) to objectively attribute unidentified occurrences to the most probable taxon based on a subset of identified records. Innovation Biodecrypt assumes that unidentified occurrences can only be attributed at certain distances from areas of sympatry. The function draws concave hulls based on the subset of identified records; subsequently, based on hull geometry, it attributes (or not) unidientified records to a given taxon. Concavity can be imposed with an alpha value and sea or land areas can be excluded. A cross‐validation function tests attribution reliability and another function optimises the parameters (alpha, buffer, distance ratio between hulls). We applied the procedure to 16 European butterfly complexes recently separated into 33 cryptic species for which most records were amalgamated. We compared niche similarity and divergence between cryptic taxa, and re‐calculated and contributed updated climatic niche characteristics of the butterflies in Europe (CLIMBER). Main conclusions Biodecrypt showed a cross‐validated correct attribution of known records always ≥ 98% and attributed more than 80% of unidientified records to the most likely taxon in parapatric species. The functions determined where records can be assigned even for largely sympatric species, and highlighted areas where further sampling is required. All the cryptic taxa showed significantly diverging climatic niches, reflected in different values of mean temperature and precipitation compared to the values originally provided in the CLIMBER database. The substantial fraction of cryptic taxa existing across different taxonomic groups and their divergence in climatic niches highlight the importance of using reliably assigned occurrence data in macroecology.

Implementation of access and benefit-sharing measures has consequences for classical biological control of weeds - Luciana Silvestri; Alejandro Sosa; Fernando Mc Kay; Marcelo Diniz Vitorino; Martin Hill; Costas Zachariades; Stephen Hight; Philip Weyl; David Smith; Djamila Djeddour; Peter G. Mason (BioControl, 2020)
The Convention on Biological Diversity and the Nagoya Protocol establish that genetic resources shall be accessed only upon the existence of prior informed consent of the country that provides those resources and that benefits arising from their utilization shall be shared. Pursuant to both agreements several countries have adopted regulations on access and benefit-sharing. These regulations have created a challenging obstacle to classical biological control of weeds. This paper reviews the experiences of Argentina, Brazil, South Africa, the USA, Canada and CABI in implementing access and benefit-sharing regulations and the implications these measures have on the effective and efficient access, exchange and utilization of biological control agents. We conclude that policy makers should be made aware of the key role biological control plays for agriculture and the environment and they are encouraged to develop tailored access and benefit-sharing legal frameworks that facilitate biological control research and implementation.

Aluminium in plasma and tissues after intramuscular injection of adjuvanted human vaccines in rats - Karin Weisser; Thomas Göen; Jennifer D. Oduro; Gaby Wangorsch; Kay-Martin O. Hanschmann; Brigitte Keller-Stanislawski (Archives of Toxicology, 2019)

From Observation to Information and Users: The Copernicus Marine Service Perspective - Pierre Yves Le Traon; Antonio Reppucci; Enrique Alvarez Fanjul; Lotfi Aouf; Arno Behrens; Maria Belmonte; Abderrahim Bentamy; Laurent Bertino; Vittorio Ernesto Brando; Matilde Brandt Kreiner; Mounir Benkiran; Thierry Carval; et al. (Frontiers in Marine Science, 2019)

The North Atlantic Aerosol and Marine Ecosystem Study (NAAMES): Science Motive and Mission Overview - Michael J. Behrenfeld; Richard H. Moore; Chris A. Hostetler; Jason Graff; Peter Gaube; Lynn M. Russell; Gao Chen; Scott C. Doney; Stephen Giovannoni; Hongyu Liu; Christopher Proctor; Luis M. Bolaños; et al. (Frontiers in Marine Science, 2019)

Aluminium toxicokinetics after intramuscular, subcutaneous, and intravenous injection of Al citrate solution in rats - Karin Weisser; Thomas Göen; Jennifer D. Oduro; Gaby Wangorsch; Kay-Martin O. Hanschmann; Brigitte Keller-Stanislawski (Archives of Toxicology, 2019)

The effects of height and BMI on prostate cancer incidence and mortality: a Mendelian randomization study in 20,848 cases and 20,214 controls from the PRACTICAL consortium - Neil M. Davies; Tom R. Gaunt; Sarah J. Lewis; Jeff Holly; Jenny L. Donovan; Freddie C. Hamdy; John P. Kemp; Rosalind Eeles; Doug Easton; Zsofia Kote-Jarai; Ali Amin Al Olama; Sara Benlloch; et al. (Cancer Causes & Control, 2015)

Y-P30 promotes axonal growth by stabilizing growth cones - Janine R. Neumann; Suvarna Dash-Wagh; Kay Jüngling; Teresa Tsai; Martin Meschkat; Andrea Räk; Sabine Schönfelder; Christian Riedel; Mohammad I. K. Hamad; Stefan Wiese; Hans-Christian Pape; Kurt Gottmann; et al. (Brain Structure and Function, 2015)

Predicting invasion in grassland ecosystems: is exotic dominance the real embarrassment of richness? - Eric W. Seabloom; Elizabeth T. Borer; Yvonne Buckley; Elsa E. Cleland; Kendi Davies; Jennifer Firn; W. Stanley Harpole; Yann Hautier; Eric Lind; Andrew MacDougall; John L. Orrock; Suzanne M. Prober; et al. (Global Change Biology, 2013)
Invasions have increased the size of regional species pools, but are typically assumed to reduce native diversity. However, global‐scale tests of this assumption have been elusive because of the focus on exotic species richness, rather than relative abundance. This is problematic because low invader richness can indicate invasion resistance by the native community or, alternatively, dominance by a single exotic species. Here, we used a globally replicated study to quantify relationships between exotic richness and abundance in grass‐dominated ecosystems in 13 countries on six continents, ranging from salt marshes to alpine tundra. We tested effects of human land use, native community diversity, herbivore pressure, and nutrient limitation on exotic plant dominance. Despite its widespread use, exotic richness was a poor proxy for exotic dominance at low exotic richness, because sites that contained few exotic species ranged from relatively pristine (low exotic richness and cover) to almost completely exotic‐dominated ones (low exotic richness but high exotic cover). Both exotic cover and richness were predicted by native plant diversity (native grass richness) and land use (distance to cultivation). Although climate was important for predicting both exotic cover and richness, climatic factors predicting cover (precipitation variability) differed from those predicting richness (maximum temperature and mean temperature in the wettest quarter). Herbivory and nutrient limitation did not predict exotic richness or cover. Exotic dominance was greatest in areas with low native grass richness at the site‐ or regional‐scale. Although this could reflect native grass displacement, a lack of biotic resistance is a more likely explanation, given that grasses comprise the most aggressive invaders. These findings underscore the need to move beyond richness as a surrogate for the extent of invasion, because this metric confounds monodominance with invasion resistance. Monitoring species' relative abundance will more rapidly advance our understanding of invasions.

Bordetella Pertussis Toxin does not induce the release of pro-inflammatory cytokines in human whole blood - Christina Bache; Ingo Spreitzer; Bjoern Becker; Bettina Loeschner; Ute Rosskopf; Kay-Martin Hanschmann; Michael Schwanig; Christian K. Schneider; Bernhard Lieb; Thomas Montag (Medical Microbiology and Immunology, 2012)

Stable isotope fractionation related to technically enhanced bacterial sulphate degradation in lignite mining sediments - Kay Knöller; Christina Jeschke; André Simon; Martin Gast; Nils Hoth (Isotopes in Environmental and Health Studies, 2012)

Downregulation of the Taurine Transporter TauT During Hypo-Osmotic Stress in NIH3T3 Mouse Fibroblasts - Daniel Bloch Hansen; Martin Barfred Friis; Else Kay Hoffmann; Ian Henry Lambert (The Journal of Membrane Biology, 2012)

Dust supply from river floodplains: the case of the lower Huang He (Yellow River) recorded in a loess–palaeosol sequence from the Mangshan Plateau - Maarten A. Prins; Hongbo Zheng; Kay Beets; Simon Troelstra; Patrick Bacon; Ilse Kamerling; Wouter Wester; Martin Konert; Xiangtong Huang; Wang Ke; Jef Vandenberghe (Journal of Quaternary Science, 2009)
The Mangshan Plateau is located on the south bank of the Huang He (Yellow River) just west of the city of Zhengzhou, well outside the Loess Plateau in central China. Mixing models of the grain‐size data indicate that the loess deposits are mixtures of three loess components. Comparison of the mixing model with existing models established for a series of loess–palaeosol sequences from the Loess Plateau indicates that the Mangshan loess has been supplied from a proximal dust source, the Huang He floodplain, during major dust outbreaks. The high accumulation rates, the composition of the loess components, and especially the high proportions of a sandy loess component support this. Owing to the exceptionally high accumulation rates, the Mangshan grain size, magnetic susceptibility and carbonate records provide a high‐resolution archive of environmental and climate change. Copyright © 2008 John Wiley & Sons, Ltd.

Phenotypes of major immediate-early gene mutants of mouse cytomegalovirus - Andreas Busche; Ana Angulo; Penelope Kay-Jackson; Peter Ghazal; Martin Messerle (Medical Microbiology and Immunology, 2008)

Contralateral muscle fatigue in human quadriceps muscle: evidence for a centrally mediated fatigue response and cross-over effect - Jodie Rattey; Peter G. Martin; Derek Kay; Jack Cannon; Frank E. Marino (Pflügers Archiv - European Journal of Physiology, 2006)

Towards a mutant map of the mouse ? new models of neurological, behavioural, deafness, bone, renal and blood disorders - Sohaila Rastan; Tertius Hough; Amy Kierman; Rachel Hardisty; Alexandra Erven; Ian C. Gray; Stepanie Voeling; Adrian Isaacs; Hsun Tsai; Mark Strivens; Rebecca Washbourne; Claire Thornton; et al. (Genetica, 2004)

Sexual selection in darkness? Female mating preferences in surface- and cave-dwelling Atlantic mollies, Poecilia mexicana (Poeciliidae, Teleostei) - Martin Plath; Jakob Parzefall; Kay E. Krner; Ingo Schlupp (Behavioral Ecology and Sociobiology, 2004)

Identification of Genes Essential for Growth at High Salt Concentrations Using Salt-Sensitive Mutants of the Cyanobacterium Synechocystis sp. Strain PCC 6803 - Inga Karandashova; Irina Elanskaya; Kay Marin; Josef Vinnemeier; Martin Hagemann (Current Microbiology, 2002)

Protection against translocating Salmonella typhimurium infection in mice by feeding the immuno-enhancing probiotic Lactobacillus rhamnosus strain HN001 - Harsharnjit S. Gill; Quan Shu; Hai Lin; Kay J. Rutherfurd; Martin L. Cross (Medical Microbiology and Immunology, 2001)

The amelioration of aluminium toxicity by silicon in wheat ( Triticum aestivum L.): malate exudation as evidence for an in planta mechanism - Kay M. Cocker; David E. Evans; Martin J. Hodson (Planta, 1998)

Non-reproduction in the honeybee mite Varroa jacobsoni - Stephen Martin; Kay Holland; Muzz Murray (Experimental and Applied Acarology, 1997)